2015
DOI: 10.3390/w7020455
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Water Supply, Sanitation, Wastewater, and Stormwater Technologies Globally

Abstract: Abstract:This paper provides an outline of history of hydro-technologies in the west and the east. It is an overview of the special issue on "the evolution of hydro-technologies globally", in which the key topics regarding the history of water and sanitation worldwide, and its importance to future cities are presented and discussed. It covers a wide range of relevant historical issues, and is presented in three categories: productivity assessment, institutional framework and mechanisms, and governance aspects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…Despite the fact that integrated water resources management action is being taken, it is still mandatory to consider climate change, global population growth and other increasing water demands for its sustainable management [44]. Furthermore, even though the results of this study revealed decreasing water demand (Table 1), to mitigate and adapt to the impact of climate change on water resources, particularly at Issyk-Kull basin, it is good to consider the hydrological weather related changes that are appearing (Figures 3 and 5) and adapt accordingly.…”
Section: Climate Change and Watermentioning
confidence: 99%
“…Despite the fact that integrated water resources management action is being taken, it is still mandatory to consider climate change, global population growth and other increasing water demands for its sustainable management [44]. Furthermore, even though the results of this study revealed decreasing water demand (Table 1), to mitigate and adapt to the impact of climate change on water resources, particularly at Issyk-Kull basin, it is good to consider the hydrological weather related changes that are appearing (Figures 3 and 5) and adapt accordingly.…”
Section: Climate Change and Watermentioning
confidence: 99%
“…We can also reach to this conclusion based on the presence of sewers which result into fields [40,41].…”
Section: Disposal and Reuse Of Wastewater In Minoan Greecementioning
confidence: 58%
“…One such solution came in the form of an aqueduct in the Roman times. However, the Minoans, who were much before their time in terms of water systems, used aqueducts before the Romans during the Bronze age [2]. The Minoans had aqueducts, a filtration system, harvested rain water, sewage pipes, etc.…”
mentioning
confidence: 99%
“…Storing water for immediate use at specific times has become the modern day equivalent of these logistical issues. The most common way to store water is to use a water tower [2].Water towers are basic water storage devices capable of holding hundreds of thousands to millions of gallons of water at a time. We can think of water towers as simply water tanks that are elevated off the ground.…”
mentioning
confidence: 99%
See 1 more Smart Citation